A COMPARISON OF THE LIFE CYCLE RITUALS OF THE MNONG ETHNIC GROUP IN DAM RONG DISTRICT (LAM DONG PROVINCE) AND DAK SONG DISTRICT (DAK NONG PROVINCE) - Thi Thuy Dung Vo (Tạp chí Khoa học Đại học Đà Lạt)
The Mnong are an ethnic minority of the Central Highlands concentrated in Dak Nong, Dak Lak, and Lam Dong provinces. In their long residence in these regions and with continuous creativity, the Mnong have created cultural characteristics shown in their customs, beliefs, and festivals. Life cycle rituals are one of them. From a comparative perspective, this article delves into the spiritual beliefs in two areas where many Mnong live, Dam Rong District (Lam Dong) and Dak Song District (Dak Nong), to find similarities and differences in the beliefs and expressions of their life cycle rituals. On that basis, some solutions are proposed to help preserve their ethnic identities through the life cycle rituals with the purpose of preserving the cultural diversity of the Mnong residents in the Central Highlands.